Lipid based therapy for ulcerative colitis: modulation of intestinal mucus membrane phospholipids as a tool to influence inflammation - Schneider, Hannah; Gauss, Annika; Füllekrug, Joachim; Stremmel, Wolfgang; Ehehalt, Robert (International journal of molecular sciences, 2010)
Ulcerative colitis (UC) is the result of an inappropriate colonic inflammatory response triggered by environmental and genetic factors. We have recently shown that mucus from UC patients has a decreased phosphatidylcholine (PC) content, while clinical trials revealed that therapeutic addition of PC to the colonic mucus alleviated the inflammatory activity. The mechanisms behind this are still unclear.
Gesehen am 20.06.2023